Tension Free Mesh Repair is an Effective Treatment of Inguinal Hernia: An Observational Study (Medicine Today, 2013)
Inguinal hernias are common and the results of surgical repair are often satisfactory but recurrence rate are variable. To prevent recurrences prosthetic materials have been increasingly used in hernia repair. In this study Lichtenstein technique of tension free mesh repair for inguinal hernia done in 140 cases in the period from July 2010 to June 2012 and outcome measured in terms of early and late morbidity especially recurrences. Seroma developed in 08 patients (5.6%) and haematoma and transient testicular swelling developed in 06 patients (4.2%) and 15 patients (10.6%) respectively. Only 2 patients (1.4%) developed wound infection and 01 patients (.71%) developed recurrences of hernia. Post operative neuralgia developed in 05 cases (3.5%). During follow up period no mesh rejection and discharging wound sinus related to presence of foreign body is observed in the study. So Lichtenstein tension free repair of inguinal hernia is safe and effective method where recurrence rate is reasonably low. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15900 Medicine Today 2013 Vol.25(1): 6-8